2020
DOI: 10.1177/1060028020975111
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants Versus Warfarin in the Treatment of Left Ventricular Thrombus

Abstract: Background Use of direct oral anticoagulants (DOACs) for the treatment of left ventricular (LV) thrombus has gained considerable interest. Objective We aimed to evaluate if DOACs are effective in the treatment of LV thrombus compared with warfarin. Methods We evaluated the medical records of patients diagnosed with a new LV thrombus at a tertiary medical center. The primary outcome was the composite of thrombus persistence, stroke, or systemic embolism. We adjusted for potential confounders using multiple logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
100
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(114 citation statements)
references
References 31 publications
13
100
0
1
Order By: Relevance
“…Nine studies reported bleeding events 6,9,16,19-22,24,25 , the risk of any bleedings was similar for NOACs and VKAs users (RR: 0.94, 95% CI: 0.67-1.31, P = 0.70; I 2 = 24%, Figure 2D ), without significant bias for publication as shown in the funnel plot ( Supplementary figure 1D) . Meta-regression showed age did not differentiate the safety of NOACs or VKAs (RR: 1.03, 95% CI: 0.81-1.31, P = 0.764, Supplementary figure 3D ).…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Nine studies reported bleeding events 6,9,16,19-22,24,25 , the risk of any bleedings was similar for NOACs and VKAs users (RR: 0.94, 95% CI: 0.67-1.31, P = 0.70; I 2 = 24%, Figure 2D ), without significant bias for publication as shown in the funnel plot ( Supplementary figure 1D) . Meta-regression showed age did not differentiate the safety of NOACs or VKAs (RR: 1.03, 95% CI: 0.81-1.31, P = 0.764, Supplementary figure 3D ).…”
Section: Resultsmentioning
confidence: 85%
“…In six studies reporting clinically relevant bleedings 6,9,16,22,24,25 , NOACs users showed more favorable outcomes (RR: 0.35, 95% CI: 0.13-0.92, P = 0.03; I 2 = 0, Figure 2E ), and no significant publication bias was detected by the funnel plot ( Supplementary figure 1E ). Age did not affect the difference in clinically relevant bleeding risk between NOACs and VKAs (RR: 0.83, 95% CI:0.41-1.69, P = 0.516, Supplementary figure 3E ).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations